2002
DOI: 10.1074/jbc.m206250200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Chaperone Function in Small Heat Shock Proteins

Abstract: To elucidate the mechanism of ␣A-crystallin chaperone function, a detailed thermodynamic analysis of its binding to destabilized, site-directed mutants of T4 lysozyme was carried out. The selected mutants form a ladder of stabilities spanning the 5-10 kcal/mol range of free energy of unfolding. The crystal structures of the majority of the mutants have been previously determined and found to be similar to that of the wild type with no evidence of static local unfolding. Complex formation between ␣A-crystallin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
79
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 57 publications
6
79
0
Order By: Relevance
“…The effect is not only seen with the highly purified recombinant preparation of ␣A-and ␣B-crystallin but also with bovine ␣ Lcrystallin (Table I). The weak binding can be inferred from the fact that the binding is reversible at least partly, and the binding affinity is low compared with that, for example, between ␣B-crystallin and the destabilized T4 lysozymes that are in the low submicromolar range (40). Here both chaperone and substrate, involved in the binding interaction, exist in states not far from the native states of the proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect is not only seen with the highly purified recombinant preparation of ␣A-and ␣B-crystallin but also with bovine ␣ Lcrystallin (Table I). The weak binding can be inferred from the fact that the binding is reversible at least partly, and the binding affinity is low compared with that, for example, between ␣B-crystallin and the destabilized T4 lysozymes that are in the low submicromolar range (40). Here both chaperone and substrate, involved in the binding interaction, exist in states not far from the native states of the proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Native state fluctuations can give rise to "ladder states," having small energy differences centering around the ground state energy (41,42). In a series of papers (40,(43)(44)(45)) from Mchaourab and co-workers, it has been demonstrated that ␣-crystallin can efficiently recognize and bind these degenerate native-like states of the substrates with varying affinity. From thermodynamic considerations, they have shown that the minor alteration in the stabilization energy of a substrate can trigger binding with the chaperone (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…But, when a nonnatural substrate carbonic anhydrase remained bound to the chaperone, further loss in subunit exchange rate was Differential Recognition of Natural and Nonnatural Substrate by Molecular Chaperone -Crystallin-A Subunit Exchange Study -Crystallin prevents the aggregation of a large variety of substrates, e.g., insulin, -lactalbumin, lysozyme, conalbumin, alcohol dehydrogenase, citrate synthase, xylose reductase, etc. [9][10][11][12][13][14][15][16][17][18][19] These substrates include proteins, which are of low molecular weight [e.g., insulin (6 kDa)], comparable to -crystallin subunit molecular weight [e.g., carbonic anhydrase (29 kDa)] and high molecular weight [e.g., alcohol dehydragenase (150 kDa)]. Besides, it recognizes substrates under various stress conditions, such as heat, disulphide cleavage, UV light exposure, oxidative stress, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it recognizes substrates under various stress conditions, such as heat, disulphide cleavage, UV light exposure, oxidative stress, etc. [9][10][11][12][13][14][15][16][18][19][20][21] These in vitro substrates belong to no particular category in terms of sequence or threedimensional structure. In addition to these ''nonnatural'' substrates, -crystallin prevents the aggregation of a number of its own substrates, which are present in the lens.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we reported the equilibrium binding of ␣A-crystallin to destabilized mutants of T4 lysozyme (24). The advantage of these mutants is that they do not aggregate on the time scale of binding and their equilibrium folding constants are in the 10 4 -10 7 range.…”
mentioning
confidence: 99%